Dix ans de lutte antifasciste 1931-1941 : mémoires - Humbert-Droz, Jules (Neuchâtel : La Baconnière, 1972)
Fonds Perrone
Frans
Monografie
Keywords: Humbert-Droz, Jules; Derde Internationale (1919-1943).; Communistische Partij van Zwitserland